(untitled) (Fiep Bulletin - online, 2014)
The lack of information and/or specific formation of the Physical Education teacher who works with people with special needs in the city of Rio de Janeiro, can be considered one of the factors which make almost impossible the true inclusion of the students in the regular classes.It can be also observed that there are others aspects involved in the poor participation of the responsible ones in the educative process, the poor accessibility of the school facilities and the poor knowledge of some pathologies.A questionnaire was made to identify the teacher’s knowledge, although this teacher be a class regent of regular classes with some students included or even of some special classes only, who has the responsibility to such thing. The principal difficulties aimed, besides the ones said already, are the lack of theorical knowledge, the lack of esperties in the area, the lack of specific material, and lack of specific law knowledge of all involved in the teaching process.